Variation in Seasonal Movement and Body Size of Wintering Populations of Black-Headed Gull in Japan - Yusuke Sawa; Hisashi Sugawa; Takeshi Wada; Tatsuo Sato; Hiroshi Arima; Norie Yomoda; Isao Nishiumi (Ornithological Science, 2025)
Bird-banding surveys are a long-established method for revealing aspects of bird migration. However, this method is often criticized for its bias in recovery or resighting locations owing to the uneven distribution of observers, and its reliance on opportunistic observations. In this study, we examined the seasonal and local movement of Black-headed Gull wintering in Japan by analyzing banding and resighting records of marked individuals, combined with morphological measurements from three wintering areas. Between 1978/79 and 2020/21, a total of 2,370 gulls were marked in Kanto, Kansai, and Kyushu. A total of 7,885 resighting records of 1,229 individuals were obtained from 1981/82 to 2022/23. The wintering populations in Kanto and Kansai were confirmed to summer on the Kamchatka Peninsula and in East Siberia, with their migration routes passing through eastern Hokkaido and along the Pacific coast of Honshu in autumn and spring. In contrast, individuals banded in Kyushu were resighted on the Korean Peninsula. Morphological measurements of these wintering populations, revealed that body size was larger in the Kanto population than in the Kyushu population. Since Black-headed Gull exhibits geographic variation in body size, it can be inferred that the wintering populations in Kanto and Kyushu originate from different breeding grounds. The Kansai population was intermediate, with no difference in body size compared with the Kanto and Kyushu populations and no distinct peaks in distribution of body size variation, indicating that it consisted of birds mixing from multiple breeding grounds. Differences in seasonal movements detected by banding/resighting records were supported by body size variation among the three areas. Black-headed Gull wintering in Japan appear to be derived from multiple breeding populations with different body size, and with the proportion of individuals from different breeding populations varying among wintering areas.